The Role of Mutual Aid Organizations in Promoting Food Sovereignty in Puerto Rican Rural Communities: A Qualitative Analysis - Mercado, Brook Lyn; Darling-Hammond, Sean (Puerto Rico Health Sciences Journal, 2026)
Previous research has shown that, during both climate and non-climate disasters—such as hurricanes, the COVID-19 pandemic, and other climate-related crises—and despite political control from the mainland United States, mutual aid organizations in Puerto Rico have played a central role in supporting community health and advancing food sovereignty. However, this research has largely focused on urban contexts and post-disaster recovery. The present study examined how mutual aid organizations in rural Puerto Rico contribute to food sovereignty through their everyday practices and beyond periods of disaster. Semistructured interviews were conducted with representatives from 5 mutual aid organizations serving rural municipalities across the island. The study findings identified 3 core themes that reflect how mutual aid organizations in rural Puerto Rico advance food sovereignty. The results suggest that mutual aid serves as a critical mechanism for decolonizing Puerto Rico’s food system, emphasizing local leadership and community-based strategies for sustainable self-determination.